The Effect of Education, R&D, and ICT on Economic Growth of Middle-Income Countries - Rabia Batool; Hamid Hasan (Journal of Management Practices, Humanities and Social Sciences, 2023)
This manuscript examines the impact of education, Research & Development (R&D) and Information and Communications Technology (ICT), on economic growth of middle-income countries using panel data set from1995 to 2019. We employ panel data set using few tests such as panel unit root test and Fully Modified Ordinary Least Square (FMOLS). The main findings indicate mobile subscriptions (proxy of ICT) has positive effect on economic growth of these countries. Education also positively influences economic growth. R&D has been observed to affect economic growth positively. This study concludes with some policy recommendations and suggestions that may be helpful for future studies. It has been found that an increase of the most educated labor force does not lead to a higher growth rate. Therefore, this study concludes that people with tertiary education must be occupied with strong human capital and cognitive skills